Preferencje ustrojowe jako czynnik dyskrepancyjny identyfikacji ideologicznych i partyjnych - Wojtasik, Waldemar (Wydział Nauk Politycznych i Dziennikarstwa UAM w Poznaniu, 2011)
Apart from its institutional dimensions, the determining factors of the evolution of a political system are based on the social expectations concerning the possible shape of the preferred and implemented solutions. This paper presents the conclusions of nationwide research carried out on a representative sample (N=1086) to analyze the direction and scope of the expected change in the political system in relation to thepolitical programs of the main political parties in Poland.
Ideological Conditioning of Preferences Concerning the Shape of the Polish Political System in the Light of Empirical Research